Educational Transformation through Digital Innovation in Qatar - Fatima Al-Hammadi (Tamilis Synex: Multidimensional Collaboration, 2025)
Digital innovation has become a strategic priority for educational transformation worldwide, particularly in countries seeking to establish knowledge-based economies. Qatar has demonstrated remarkable progress in integrating digital technologies into its education system through comprehensive national policies, substantial investments in educational infrastructure, and the promotion of innovative teaching and learning practices. This study explores the role of digital innovation in transforming education in Qatar by examining its contributions to teaching effectiveness, student engagement, institutional management, and educational sustainability. Using a qualitative library research approach, the study synthesizes findings from peer-reviewed journal articles, policy documents, and international reports related to educational digitalization. The findings indicate that digital innovation enhances learning accessibility, strengthens teachers' digital competencies, supports personalized learning, and improves institutional efficiency through data-driven decision-making. Nevertheless, challenges remain, including unequal digital competencies, cybersecurity concerns, technological infrastructure disparities, and the need for continuous professional development. The study concludes that successful educational transformation requires not only advanced technologies but also supportive leadership, inclusive educational policies, and sustained investment in human capital. Qatar's experience provides valuable insights for other countries pursuing digital transformation in education while maintaining quality, equity, and long-term sustainability